Development of Re-Creative Strategies in Learning to Write Poetry for Elementary School Students - Aryadi, Aryadi; Sudaryono, Sudaryono; Karim, Maizar (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2022)
Research aims to produce a strategy of learning to write poetry through re-kreari (re-creation) made it easier for students to write poetry. This type of research is research and development R & D which aim develop learning strategies to write poetry for elementary school students with a re-creation (re-creation) so that elementary school students can deft writing poetry with a choice for the right words.The results of this study showed that the overall strategy of learning to write poetry through re-creations with either category. Design strategies worth learning strategy design expert for your implementasik can be used to guide the development of learning strategies. From the responses of teachers and students during field trials gave a positive assessment of the strategies developed. At trial students commented that the implementation of learning outside the classroom carried over to more easily find new ideas.Based on the results of data analysis, the results of the validation experts generally stated that the strategy of learning to write poetry through re-creations for learning to write poetry free elementary school students. With the recommended this strategy in teaching.